Role of atrial natriuretic peptide in the dissociation between flow relations with ventricular mass and function in a community with volume-dependent hypertension - Yusuf, Suraj M.; Norton, Gavin R.; Peterson, Vernice R.; Mthembu, Nonhlanhla; Libhaber, Carlos D.; Tade, Grace; Bello, Hamza; Bamaiyi, Adamu J.; Mmopi, Keneilwe N.; Dessein, Patrick H.; Peters, Ferande; Sareli, Pinhas; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: Whether differential effects of volume load on left ventricular mass (LVM) and function occur in sustained volume-dependent primary hypertension, and the impact of atrial natriuretic peptide (ANP) on these effects, is unknown. Methods: From aortic pressure, velocity and diameter measurements and echocardiography, we determined in an African community (n=772), the impact of systemic flow-induced increases in central pulse pressure (PPc) and circulating ANP (ELISA) on LVM and indexes of function. Results: Stroke volume (SV), but not aortic flow (Q), was associated with LVM and mean wall thickness (MWT) beyond stroke work and confounders (p<0.0001). Adjustments for SV markedly decreased the relationships between PPc and LVMI or MWT. However, neither SV, nor Q were independently associated with either myocardial s’, e’, or E/e’ (p>0.14) and adjustments for neither SV nor Q modified relationships between PPc and s’, e’ or E/e’ (p<0.005 to <0.0001). SV was nevertheless strongly and independently associated with ANP (p<0.0001) and ANP was similarly strikingly associated with s’ (p<0.0001) and e’ (p<0.0005), but not E/e’, independent of confounders and several determinants of afterload. Importantly, ANP concentrations were inversely rather than positively associated with LV diastolic dysfunction (DD) (p<0.005) and lower rather than higher ANP concentrations contributed markedly to the ability to detect DD in those with, but not without LV hypertrophy. Conclusion: In populations with sustained volume-dependent hypertension, flow (SV)-related increases in PP have a major impact on LV structure, but not on function, an effect attributed to parallel striking beneficial actions of ANP on myocardial function.